2021
DOI: 10.2147/dddt.s290030
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Improves Cognitive Function of Alzheimer’s Disease Mice by Regulating SSTR4 Ubiquitination

Abstract: Purpose Many researches have investigated the functions of tetramethylpyrazine (TMP) in Alzheimer's disease (AD). This study aimed to discuss the underlying mechanism of TMP in AD mice. Methods TMP (200 mg/kg) was administered to 6-month-old APP/PS1 transgenic mice, and behavioral changes and hippocampal nerve injury in AD mice were detected. Apoptosis and autophagy-related protein levels were detected. Changes in gene expression before and after TMP treatment were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In vivo, TMP treatment improved the learning and memory function, attenuating AD mice’s cognitive impairment. The potential mechanism might be related to reducing the ubiquitination of SSTR4, thus increasing its levels in the system ( Weng et al, 2021 ). Apart from these, researchers have designed the ligustrazine phosphate (LP) transdermal ethosomal system, and evaluated the effect of LP on AD in scopolamine-induced amnesia rats.…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%
“…In vivo, TMP treatment improved the learning and memory function, attenuating AD mice’s cognitive impairment. The potential mechanism might be related to reducing the ubiquitination of SSTR4, thus increasing its levels in the system ( Weng et al, 2021 ). Apart from these, researchers have designed the ligustrazine phosphate (LP) transdermal ethosomal system, and evaluated the effect of LP on AD in scopolamine-induced amnesia rats.…”
Section: Effects Of Tetramethylpyrazine On Central Nervous System Dis...mentioning
confidence: 99%
“…Somatostatin receptor 4 (SSTR4), mainly distributed in the cortex and hippocampus, is crucial in learning and memory. SSTR4 can upregulate Aβ-degrading enzyme expression in the hippocampus, whereas ubiquitin-mediated degradation of SSTR4 initiates neuronal apoptosis in AD pathogenesis [ 8 ]. Cullin 4B (CUL4B) overexpression promotes SSTR4 ubiquitination, resulting in AD exacerbation [ 8 , 136 ].…”
Section: Mhdi-mediated Attenuation Of Aβ-induced Apoptosismentioning
confidence: 99%
“…SSTR4 can upregulate Aβ-degrading enzyme expression in the hippocampus, whereas ubiquitin-mediated degradation of SSTR4 initiates neuronal apoptosis in AD pathogenesis [ 8 ]. Cullin 4B (CUL4B) overexpression promotes SSTR4 ubiquitination, resulting in AD exacerbation [ 8 , 136 ]. In 2020, Weng et al demonstrated that tetramethylpyrazine, extracted from Ligusticum wallichii , attenuates cognitive impairment by downregulating CUL4B/SSTR4-mediated apoptotic signaling in the hippocampus at 30 days in APP/PS1 mice [ 8 ].…”
Section: Mhdi-mediated Attenuation Of Aβ-induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ligustrazine has been shown to activate PPARγ and promote mitophagy by inducing Parkin translocation to the mitochondria [ 38 , 40 ]. Importantly, ligustrazine improves cognitive impairment in rodent models of AD [ 13 , 35 ], suggesting that ligustrazine may become a novel drug candidate for the treatment of AD. However, the short elimination half-life of ligustrazine seriously limits its application in clinical practice [ 41 ].…”
Section: Introductionmentioning
confidence: 99%